General Statutory Obligations under MSME and Union Budget 2024-25 - Dr. H M Naveen (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
Establishment of a National Board for MSMEs headed by the Minister of MSME is to examine factors affecting the promotion and development of MSMEs across the nation. It provides the legal framework for the concept of ‘enterprise’ which comprises both manufacturing and service entities. The MSMED Act empowers the Central Government to undertake programmes and issue guidelines to develop the competitiveness of MSMEs. Keeping this in view, the Ministry is committed towards the use of Official Language “Hindi” in all the attached offices under the M/o MSME. Besides this, the Ministry is implementing the guidelines/instructions issued by the Department of Personnel and Training and the Central Vigilance Commission in creating greater awareness of vigilance among the users of its services. Even Citizens’/Clients’ Charter for M/o MSME have been prepared and the same can be viewed at Ministry’s website. This Charter consists of a Declaration of the Ministry, incorporating its mission and commitment to the MSMEs and for the people of India, in general. Under the RTI Act, 2005, Citizens may approach the Public Information Officer (PIO) on any working day. The complete information in respect of the Ministry and other Public Authorities of the Organizations under this Ministry is regularly uploaded on the website of the Ministry. An Internal Complaints Committee has been constituted in the Ministry to prevent Sexual Harassment of Women at Work Place. “She-box (Sexual Harassment Electronic-Box) has been introduced by the Ministry of W & C Development to enable women employees to file complaints through online. These Statutory Obligations under MSME are discussed in detail in this article.